The challenges and opportunities of translating best practice immunisation strategies among low performing general practices to reduce equity gaps in childhood immunisation coverage in New Zealand - Nikki M. Turner; Nadia A. Charania; Angela Chong; Joanna Stewart; Lynn Taylor (BMC, 2017)
Abstract Background Immunisation coverage rates vary considerably at the local level across New Zealand and challenges remain with effectively translating best available research evidence into public health practice. This study aimed to translate best practices from high performing general practices into strategies to improve childhood immunisation coverage among low performing practices. Methods An intervention study was undertaken of general practices with low immunisation coverage rates and a high percentage of the enrolled population being of Māori ethnicity. Intervention groups received customised action plans and support for a 12 month period while control groups received 'business as usual' support. Structured interviews were conducted with key informants from all participating practices to understand current aspects related to childhood immunisation delivery and surveys were conducted to understand how the intervention worked. Collected data were thematically analysed. Results Ten sites were randomised to either intervention (n = 6) or control group (n = 4). Positive aspects of childhood immunisation delivery included high prioritisation at the practice and staff being pro-immunisation and knowledgeable. Key challenges experienced included inaccurate family contact information and discrepancies with referral processes to other providers. Other challenges noted were building rapport with families and vaccine hesitancy. The action plans included various strategies aimed to improve processes at the practice, contact and engagement with parents, and partnership development with local service providers. Conclusions Creating customised action plans and providing support to providers were considered as helpful approaches when attempting to improve childhood immunisation coverage rates. Our study supports the notion that one strategy will not solely by itself improve childhood immunisation rates and highlights the importance of having a toolkit of strategies from which to draw from.